Corporate social responsibility and its impact on organizational attractiveness: Unveiling the mediating role of perceived organizational support - Shimmy Francis; Sangeetha Rangasamy; Sathiyaseelan Balasundaram; Lakshmi Shankar Iyer; Elangovan N. (Cogent Business & Management, 2024)
The central aim of the study is to investigate the mediating role of perceived organizational support (POS) in the relationship between corporate social responsibility (CSR) initiatives and organizational attractiveness (OA). It employs a cross-sectional quantitative design, collecting data from diverse organizations. Multistage convenient sampling was used to collect responses from employees of 20 IT companies in Bengaluru. Insights from employees working in IT companies are collected through the questionnaire. There were 740 questionnaires distributed, of which only 396 were returned in their completeness state. Statistical analyses, including regression and bootstrapping techniques, were done using SPSS and AMOS to examine the mediating effect of POS. The study highlights a noteworthy mediating effect of perceived organizational support (POS) on the relationship between CSR initiative and organizational attractiveness. It was also revealed that POS partially mediates CSR and OA, significantly influencing CSR and OA. Managerial implications of this study are that the organization focusing primarily on employee support measures enhances the external reputation and develops internal commitment and loyalty. These insights furnish organizations with a strategic roadmap to navigate the dynamic realm of CSR and organizational attractiveness.
Keywords: 650; Organizational attractiveness; corporate social responsibility; perceived organizational support; information technology; structural equation modeling; catchment; Stakeholder theory